Design and Implementation of Arduino and Ultrasonic Sensors based Smart Cane for Visually Challenged:A Practical approach - Monira, C S; Biswas, V; Adhikary, S; Maity, S (International Journal of Computer Sciences and Engineering, 2025)
According to the WHO there is 39 million blind present across the globe. These visually challenged group faces lot of difficulties in various task including basic orientation and mobility. We worked in two phase. In phase one this paper describes the design and implementation of a smart cane which is consists of Arduino and Ultrasonic Sensor. The stick is made up of a microcontroller, GPS Module, Buzzer, Vibrator, Vibrator goggles, Bluetooth and head phone connections. The Arduino can control the surroundings environmental obstacles by receiving the input signals. A buzzer is operated by a transducer and it converts an electric, oscillating signal in the audible range of 20Hz to 20 kHz. A vibrator motor is included along with buzzer to enhance its capacity to receive information’s from the environment in various formats. In addition to this the sound signal can also be transferred to the user’s ears with the help of output to an earphone. This walking stick can give response in various conditions like obstacle detections, wet surface detection, Heat detection, IR sensor, LDR sensor. In phase two we used our newly made smart cane for the practical demonstration. For this, we have used National Orientation and Mobility checklist (NOMA) pre and post usage of the cane among 20 blind individuals. Paired t test results shows there is significant changes (p<0.0001) in their mobility performances with this newly made cane. The features of light weight, easy to use and cheaper cost will make it more acceptable to the users.